PENGARUH STRESS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA CV DUA TUKANG FURNITURE TANGERANG SELATAN - Putri Puspitasari, Diva; Nelsi, Mitri (Journal of Research and Publication Innovation, 2024)
Work stress and the work environment play an important role in improving employee performance. This research aims to examine the effect of work stress and the work environment on employee performance at CV. Two Furniture Craftsmen. The population in this study were all CV employees. Two Furniture Craftsmen and the research sample was 53 employees. Data analysis using multiple simple linear regression, classical assumption tests, hypothesis testing and coefficient of determination. The results of this research show that simultaneously the work stress and work environment variables have a significant effect on employee performance. Simultaneously work stress (X1) and work environment (X2) have on employee performance (Y) with a correlation value of 0.921, meaning they have a strong influence. Coefficient of determination 84.8%. Hypothesis testing obtained f count > f table or (136.951 > 3.183). Thus, Ho is rejected and Ha is accepted, so from this research it can be concluded that there is a positive and significant influence between the variables Job Stress (X1) and Work Environment (X2) on employee performance (Y) CV. Two Furniture Craftsmen.